CRETACEOUS OCEANIC ANOXIC EVENTS IN WESTERN CONTINENTAL GREECE - Karakitsios, V.; Tsikos, H.; Van Breugel, Y.; Bakopoulos, I.; Koletti, L. (Bulletin of the Geological Society of Greece, 2018)
Integrated chemostratigraphy and biostratigraphy in Cretaceous pelagic carbonate successions and associated organic sediments of the Ionian basin (western Greece) show the first documentation of the Cenomanian Turonian (OAE)2 and Lower Albian (OAE)1b Oceanic Anoxic Events from western Greece. Preliminary study of the Pindos basin (western Greece) has also identified a black shale horizon which may corresponds to the Lower Albian (OAE)1b Oceanic Anoxic Event.